Review : Bathymetry Mapping Using Underwater Acoustic Technology - Muhammad Zainuddin Lubis; Sri Pujiyati; Budhi Agung Prasetyo; Tiggi Choanji (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
The bathymetry mapping using underwater acoustic technology very important in Indonesia waters. Bathymetry is the result of measuring the height of the seabed so that the bathymetric map provides information about the seabed, where this information can provide benefits to several fields related to the seabed. In bathymetry mapping uses underwater acoustic technology where among them is using Single beam echosounder and MBES (Multibeam Echosounder System), and multibeam echosounder (MBES) is acoustic equipment that is intensively used frequently in basic waters mapping. The advantage of using underwater acoustic technology is the acquisition and processing of data in real time, high accuracy and precision (correction of the bathymetry data was carried out with reference to the 2008 International Hydrographic Organization (IHO), and cannot be a threat or damage to objects. Retrieval of bathymetry data must use parallel patterns, namely: patterns with perpendicular sounding directions and tend to be parallel to longitudinal lines or in accordance with parallel sounding patterns.